2017
DOI: 10.1186/s40035-017-0078-4
|View full text |Cite
|
Sign up to set email alerts
|

The role of cognitive activity in cognition protection: from Bedside to Bench

Abstract: BackgroundCognitive decline poses a great concern to elderly people and their families. In addition to pharmacological therapies, several varieties of nonpharmacological intervention have been developed. Most training trials proved that a well-organized task is clinically effective in cognition improvement.Main bodyWe will first review clinical trials of cognitive training for healthy elders, MCI and AD patients, respectively. Besides, potential neuroprotective and compensatory mechanisms in animal models of A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 208 publications
(201 reference statements)
2
12
0
Order By: Relevance
“…These results suggest that individuals with MCI who received multicomponent forms of training or used interventions which targeted multiple cognitive domains (including lifestyle changes) also demonstrated small – moderate improvements on measures of cognition post-intervention. This is consistent with other reviews which found support for multidomain forms of intervention (Ballesteros et al 2015 ; Bamidis et al 2014 ; Li et al 2011 , 2014 , 2017 ; Maffei et al 2017 ; Suo et al 2016 ; Yin et al 2014 ). Regarding the other interventions examined, there was insufficient evidence to offer greater clarification of effects by cognitive domain or type of training.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…These results suggest that individuals with MCI who received multicomponent forms of training or used interventions which targeted multiple cognitive domains (including lifestyle changes) also demonstrated small – moderate improvements on measures of cognition post-intervention. This is consistent with other reviews which found support for multidomain forms of intervention (Ballesteros et al 2015 ; Bamidis et al 2014 ; Li et al 2011 , 2014 , 2017 ; Maffei et al 2017 ; Suo et al 2016 ; Yin et al 2014 ). Regarding the other interventions examined, there was insufficient evidence to offer greater clarification of effects by cognitive domain or type of training.…”
Section: Discussionsupporting
confidence: 89%
“…In this instance, training may act on primary networks and complementary processes simultaneously requiring integration of complex skillsets, including lifestyle changes, mitigating structural and functional declines by enhancing processing in specific centers and decreasing the neural burden on other areas (Barban et al 2017 ; Hosseini et al 2014 ; Suo et al 2016 ). Multidomain approaches may also target multiple neural regions for a more enriched and complex neural challenge (Ballesteros et al 2015 ; Li et al 2017 ). Moreover, multidomain approaches may offer greater utility as most cognitive skills are not unitary, single-domain processes but involve interrelated cognitive functions across several areas which, after training, prompt inclusion of additional networks (Belleville et al 2011 ).…”
mentioning
confidence: 99%
“…Non-pharmacological interventions have shown advantages in delaying cognitive ability declining (Li et al, 2017). There are various approaches, including cognitive training, physical exercise, and diet modification (Olazaran et al, 2010; Buschert et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…These devices can be used separately or in combination with a computer, a smartphone, or an iPad when self-monitoring PA (PA selfmonitoring technologies). Compared to PA, fewer behavior change techniques for cognitive and social activities have been reported, although numerous studies have identified the relationships between these activities and health outcomes [6,7]. We showed that the probability of dementia is significantly lower in individuals who had an active lifestyle including daily conversation, driving a car, shopping, and field work or gardening using longitudinal observational data [8].…”
Section: Introductionmentioning
confidence: 77%
“…These devices can be used separately or in combination with a computer, a smartphone, or an iPad when self‐monitoring PA (PA self‐monitoring technologies). Compared to PA, fewer behavior change techniques for cognitive and social activities have been reported, although numerous studies have identified the relationships between these activities and health outcomes [6,7].…”
Section: Introductionmentioning
confidence: 99%